The Influence of the Level of Knowledge of Halal Certification Law on the Interest of MSMEs in Registering Halal Products - Taufan Perdana Putra; Novita Setyoningrum; Galuh Arga Dinata Sagitr (LEGAL BRIEF, 2025)
The implementation of Law Number 33 of 2014 concerning Halal Product Assurance faces significant challenges in the Micro, Small, and Medium Enterprises segment, particularly related to low participation in the halal certification scheme. This study aims to analyze the influence of the level of legal knowledge of halal certification on the interest of MSMEs in registering halal products in Blitar Regency, East Java. Using a quantitative approach with a cross-sectional survey design, the study involved 97 respondents from the food and beverage sector MSMEs who did not yet have halal certification. Data were collected through a structured questionnaire based on a Likert scale and analyzed using simple linear regression. The results showed a positive and significant influence of legal knowledge on certification interest with a regression coefficient of 0.444 and a significance value of p<0.001, indicating that increased understanding of the substantive, procedural, and sociological dimensions of halal certification regulations will accelerate business actors' intentions to access the certification scheme. This finding confirms the relevance of legal knowledge as a crucial determinant of MSME regulatory compliance, although it only explains 15.3% of the variation in interest, indicating the need to explore complementary factors. The practical implications of the research emphasize the urgency of transforming the legal information dissemination strategy from a sporadic socialization pattern to a systematic and sustainable participatory educational approach.